1997
DOI: 10.1089/dna.1997.16.533
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Characterization of the Human Cytosolic Malic Enzyme Promoter: Thyroid Hormone Responsiveness

Abstract: We report the structural and functional features of the 5'-flanking region of the human cytosolic malic enzyme (ME) gene. A 2.2-kb subclone, comprising 1.5 kb upstream of the translation initiation codon, the first exon, and 0.7 kb of flanking intronic region, was sequenced and mapped to chromosome 6. The proximal promoter region is rich in G + C, lacks TATA or CCAAT boxes, and shows multiple transcription start sites, the major one 106 nucleotides upstream the ATG codon. Sequences -59/-13 and -137/-103 confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…TaqMan reactions were carried out with the TaqMan universal PCR master mix (Applied Biosystems, Branchburg, NJ) in a total volume of 25 mL on an ABI-PRISM 7000 Sequence Detector (Applied Biosystems). Oligonucleotide primers and the TaqMan probes for SPAK [27] and ME1 [28] mRNAs were designed according to published sequences with the Primer Express 2.0 program (Applied Biosystems). Primers and probe for glyceraldehyde-3-phosphate dehydrogenase (GAPDH), PSA, and CDNK1A mRNAs were purchased from Applied Biosystems.…”
Section: Real-time Pcr Quantitation Of Mrnamentioning
confidence: 99%
“…TaqMan reactions were carried out with the TaqMan universal PCR master mix (Applied Biosystems, Branchburg, NJ) in a total volume of 25 mL on an ABI-PRISM 7000 Sequence Detector (Applied Biosystems). Oligonucleotide primers and the TaqMan probes for SPAK [27] and ME1 [28] mRNAs were designed according to published sequences with the Primer Express 2.0 program (Applied Biosystems). Primers and probe for glyceraldehyde-3-phosphate dehydrogenase (GAPDH), PSA, and CDNK1A mRNAs were purchased from Applied Biosystems.…”
Section: Real-time Pcr Quantitation Of Mrnamentioning
confidence: 99%
“…GonzalezManchon et al [84] have suggested that, in the absence of T 3 , binding of T 3 receptors homodimers to T 3 RE represses human malic enzyme gene expression. These homodimers would dissociate from the T 3 RE when T 3 is present and the receptors could then heterodimerize with RXRα, this new complex activating malic enzyme gene expression.…”
Section: Ligands For Nuclear Receptorsmentioning
confidence: 99%
“…Ovine and human sequences show 86% identity in the region −224/−92, 84% identity in the region −744/−682 and 87% identity in the region −1126/−1075. The region corresponding to the major transcription start site of the human ME1 gene (González-Manchón et al, 1997) is also conserved in the ovine sequence (Fig. 1).…”
Section: Resultsmentioning
confidence: 97%
“…As in human, rat and chicken (Morioka et al, 1988;Hodnett et al, 1996;González-Manchón et al, 1997), the ovine ME1 promoter contains no TATA-box upstream of the transcription start site. Similar to the other species, the region proximal to the translation start site has a high GC content (76% from −473 to −1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation